Islamic Religious Education Learning Strategy with Edutainment Insight in Improving Learning Motivation of Student - Choerul Huda; Muhammad Hanief; Dian Mohammad Hakim (Nazhruna: Jurnal Pendidikan Islam, 2022)
This article is to find out how the educational planning of Islamic religious education with edutainment perspective in increasing the motivation of the students in the implementation of Islamic religious education with the educational perspective in increasing the motivation of the students and the evaluation of Islamic religious education with the perspective of edutainment in increasing the motivation of the students. This study uses a qualitative descriptive approach based on observations made in a participatory way on a social phenomenon. The results of this study are first, this educational learning plan was developed by students of SMA Al Muhammad Cepu in the implementation of memorizing chapter 30, and memorizing 1,000 hadiths accompanied by habituation, after praying before the start of learning, continued reading juz 30, carried out every morning students to get used to reading juz 30 and 1000 hadiths so that their memorization is maintained. Second, the teaching and learning activities implemented at Al Muhammad Cepu High School, which are related to the IRE folder and have been categorized religiously, include fiqh, Ta'lim, Islamic boarding school, and also the Al Qur'an Tahfidz. Third, changing the learning in the classroom into the letter U or like a meeting table, providing a pamphlet of icons/symbols in doing learning and giving calligraphy writing taken from hadith and wise words and can also make fampet able to motivate students through the pamphlet.